Implementasi dan Pengujian Rangkaian Inverter Daya Rendah Berbasis Multivibrator - Muhammad ‘Atiq; Danang Syam Qhodarus; Raka Dian Mahardi; Sigit Prakosa A N; Danang Hendrawan; Rizal Agri Wahyuadi (Lembaga Pengembangan Kinerja Dosen, 2025)
This research focuses on the design, implementation, and testing of a DC-to-AC inverter circuit utilizing an astable multivibrator configuration. The primary objective of this study is to convert a 12-volt DC input voltage, typically obtained from a battery or other low-voltage sources, into a standard 220-volt AC output voltage suitable for powering common household and industrial appliances. Inverters play a crucial role in power electronics, enabling the efficient use of renewable and portable energy systems. The research method involved several stages, beginning with circuit design based on an astable multivibrator schematic. Components including C1815 and TIP31C transistors, resistors, capacitors, and a step-up transformer were carefully selected and assembled onto a printed circuit board (PCB). After the circuit was successfully constructed, testing was carried out by supplying a 12-volt DC source and measuring the resulting voltage values using a digital multimeter. The experimental results demonstrated that the inverter circuit was able to effectively convert the input voltage into an alternating output, producing an average of 228 volts AC. This indicates that the designed circuit not only functioned according to expectations but also operated with a high degree of accuracy. Overall, the findings highlight the practicality and reliability of the astable multivibrator inverter for low-power conversion applications. Furthermore, the study contributes to a deeper understanding of inverter circuit design and offers a foundation for further development of efficient, low-cost, and accessible power conversion systems.